Penerapan Metode Inkuiri dalam Meningkatkan Keterampilan Berfikir Kritis Dan Keaktifan Belajar Siswa pada Mata Pelajaran PAI Di MTS Al-Amin Pekalongan - Failasuf Fadli (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
Students' lack of understanding in the learning process of Islamic Education (Islamic Education) material in schools is one of the problems that is often encountered in schools. In addition, students are also not enthusiastic in responding to the material presented by their teacher. Such behavior is because the PAI material is considered less attractive, besides the use of monotonous learning models makes students less active and unable to develop skills in critical thinking. This can be seen from the behavior of students in the class who tend to only see and hear the subject matter provided by the teacher. Meanwhile, PAI learning is an effort to equip students with knowledge, understanding, and values that come from Islamic teachings. To achieve maximum learning outcomes, the teacher is expected to be able to apply a learning method that can develop students' thinking patterns. One of the learning methods referred to is the inquiry learning method. The implementation of the inquiry method in Islamic Education subjects can increase critical thinking power and student activity in the teaching and learning process. This study used a qualitative research method with the primary source of teachers who taught PAI subjects (Fiqh, al-Qur'an Hadith, Aqidah Akhlak, Islamic Cultural History) and students of MTs Al-Amin Pekalongan. This research process through the stages of data reduction, data presentation and drawing conclusions. The results of this study show that inquiry learning which maximally involves the students' brain ability to think, search for and investigate a problem raised by the teacher systematically and logically will have an impact on students so that students can find their own knowledge, attitudes and skills in answering problems said his teacher. By using all the knowledge that students have, it can move the soul and lead to the ability to think critically and actively.